TRANSFORMASI DIGITAL PELAYANAN AKADEMIK PADA PONDOK PESANTREN RIYADHUS SHOLIHIN BERBASIS E-AKADEMIK - Dona Kurnia; Sadar, Sadar Martua Haholongan Sir; Azim, Fauzan Azim (Unit Pelaksana Praktik Kependidikan Terpadu Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Riau, 2025)
Education is a crucial aspect of life. The progress of a nation can often be measured by the quality of education implemented within it. In today's era, education has undergone remarkable transformations. However, in the context of the modern world, educational services face increasingly complex challenges. These challenges include demands for greater efficiency, accessibility for diverse groups, and alignment with technological advancements and current needs. Pondok Pesantren Riyadhus Sholihin also faces challenges in its educational services due to the continued use of manual systems. Issues include manual recording of student assessments without long-term secure storage solutions, difficulties for teachers in setting class schedules, and a manual reporting system, making data access inconvenient and inefficient. To address these challenges, digital transformation is essential, particularly through the development of an e-academic system Information. This study employs the R&D (Research and Development) methodology with stages of define, design, develop, and disseminate. Additionally, system development adopts the SDLC (System Development Life Cycle) model. E-Academic applications are built using the PHP and MySql programming languages The study results show that the developed e-academic system effectively addresses these challenges. It enables real-time access to student grades and reports, provides secure data storage, simplifies teachers' tasks in setting class schedules, and delivers various other benefits, making the system efficient and effective for Pondok Pesantren Riyadhus Sholihin.